Imagining common times: an era according to young artists during their time at Balmaceda Arte Joven - Cayupi País, Malen; Medina López, Camila (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
Imagining Common Times compiles the experiences of young participants in artistic training workshops conducted by Balmaceda Arte Joven in the context of the 2019 social upheaval and the pandemic. Analyzing these young participants’ narratives, the book shows how these events transformed their daily life and identities during their transition from protests to confinement adaptation, and how it impacted their creativity and critical thinking. This review also reflects on the role of art in times of social and political crisis, opening up new avenues for research on the role of academic inquiry in artistic and cultural institutions.